Perspectives on biological catalysis - Benkovic, Stephen (Henry Stewart Talks, 2007)
How do enzyme motions and fluctuations impact catalysis?, Are the times scales for protein structural changes and the enzymatic catalytic cycle similar?, How are electrostatics modulated in enzyme active sites in conjunction with catalysis?, Dihydrofolate reductase as a model: kinetics, reactions & structure
Updated at 2017/07/31